Inter-generational transition strategy assessment: the case of Rosburg farms - Rosburg, Britney (Kansas State University, 2017)
Rosburg Farms is a crop farm in Northwest Iowa that specializes in corn and soybean production. The oldest farm operator, Richard was looking ahead to retirement while the next generation, Brian has been working to identify an entry strategy into the operation as a beginning farmer. The purpose of this research was to identify and evaluate candidate alternatives that Brian could bring to Rosburg Farms and to understand if the operation was at a point where Brian was needed as full time labor. Three candidate scenarios including renting additional crop acreage, building a hog facility, and building a poultry layer house were evaluated via SWOT analyses. The SWOT analysis results indicated that renting additional crop acres was the best candidate alternative for the farming operation. To understand how adding the additional acreage to crop production affects the timeliness of the operation and to identify binding resources a whole-farm linear programming planning model was parameterized. Parameters included available labor, machinery, days suitable for field work, crop rotations and available acreage. Production enterprise budgets for corn and soybean production and a projected cash flow were developed to understand if this acreage expansion would be profitable for the multi-family farming operation. The results of the planning model indicated that the field work operations would be completed with the available labor, machinery, and days suitable for fieldwork. The production budgets and cash flow results indicated that Rosburg Farms would remain profitable once farm size was expanded with additional rented acreage. Considering Brian employed off the farm, it was not necessary for him to quit his job to farm full time at this point. Future analysis should be used to understand at what farm size are needed to justify Brian leaving his off-farm employment to farm full time. These results are applicable beyond the Rosburg farm and are of interest to beginning farmers, farms anticipating transition to next generation, and professional specializing in succession planning.
Keywords: Linear Programming; Transition; Beginning Farmer; Rural Household; Succession Planning